An ICT Use Case of Social Business Based on the Business Model Perspective - Tetsuji Ogawa; Hiroyasu Yuhashi; Masakatsu Nishigaki (International Telecommunications Society (ITS), 2017)
Social businesses that solve local social problems using business methods have gained attention lately. Using information and communication technology (ICT) to solve social problems is expected to create social innovation that is compatible with social missions and business feasibility; however, the mechanism has not been clarified. In this research, a successful social business is analyzed with a focus on ICT and social capital, and attempts are made to define the mechanism of social innovation. The case of a direct sales store at a local roadside station was used to conduct a business model analysis using interviews to collect data. As a mechanism of social innovation, social capital has smoothly introduced ICT and strategic change, and the introduction of ICT changed the business model from a horizontal division type to a vertical integration type.
Keywords: 330; Social Innovation; Business Model; Social Capital